Target populations and treatment cost for bempedoic acid and PCSK9 inhibitors: a simulation study in a contemporary CAD cohort. (14th October 2021) - Blaum, C; Brunner, F J; Kroeger, F; Bay, B; Gossling, A; Lorenz, T; Graef, A; Zeller, T; Schnabel, R; Clemmensen, P; Westermann, D; Blankenberg, S; et al.
Abstract: Background: The 2019 ESC dyslipidaemia guidelines recommend a more intense LDL-cholesterol (LDL-C) reduction for patients with coronary artery disease (CAD). As a result the need for PCSK9 inhibitors (PCSK9i) is projected to increase significantly, with a concomitant substantial impact on treatment cost. Adding the novel lipid lowering agent bempedoic acid (BA) to established oral lipid lowering therapy could provide an affordable alternative to PCSK9i to attain the LDL-C treatment target, particularly in patients with statin intolerance. Aims: To quantify the target populations for BA and PCSK9i as well as the related treatment costs to achieve the LDL-C target of the 2019 ESC dyslipidaemia guidelines assuming addition of BA to lipid lowering medication. Methods: We included 1922 patients (mean age 69.3 years) with angiographically documented CAD from an observational cohort study ongoing since 2015. A Monte Carlo simulation incorporating an algorithm for intensification of lipid lowering medication was applied in order to achieve the LDL-C treatment goal of <55 mg/dL and a ≥50% reduction from baseline LDL-C. The algorithm added sequentially a statin, ezetimibe, optionally BA, and a PCSK9i, and considered both partial and total statin intolerance. Two scenarios of treatment intensification were simulated for both a moderate (2% full and 10% partial) and a high rate of statin intolerance (12% full): 1. without BA and 2. with BA. Treatment costs and preventable events were calculated for each scenario and the following annual medication cost in Germany: €6049 evolocumab, €1551 BA. Results: Figure 1 displays the baseline LDL-C distribution (median LDL-C 86.0 mg/dL) and lipid lowering medications. The need for PCSK9i in scenario 1 would be 41.4% for a moderate and 46.1% for a high rate of statin intolerance. Addition of BA in scenario 2 would reduce the need for PCSK9i to 25.3% and 29.4%. Figure 2 displays the LDL-C distributions and lipid lowering medications for scenarios 1 and 2 assuming a moderate rate of statin intolerance. Use of BA would lower the annual overall treatment cost incurred through use of PCSK9i ± BA per 1, 000, 000 CAD patients by 13.3% and 10.5%. The cost per prevented event in the entire cohort would be lower (−5.0 and −6.3%), however at the price of less prevented cardiovascular events (−8.7% and −4.5%). Amongst patients with full statin intolerance, the cost per prevented event would be reduced (−6.8% for both rates of statin intolerance) whilst more cardiovascular events would be prevented (+7.5% and +6.9%). Conclusion: Use of BA in patients with CAD would reduce the need for PCSK9i as well as the overall treatment cost for add-on lipid lowering therapy. The subpopulation of patients with full statin intolerance might profit particularly. Funding Acknowledgement: Type of funding sources: None.